International pecking order - Eren, Egemen,Malamud, Semyon,Zhou, Haonan (Swiss Finance Institute, 2022)
We document that corporates in emerging markets borrow more in foreign currency when the local currency provides a better hedge in downturns. We develop an international corporate finance model in which firms facing adverse selection choose the foreign currency share of their debt. In the unique separating equilibrium, good firms optimally expose themselves to currency risk to signal their type. The nature of this equilibrium crucially depends on the co-movement between cash flows and the exchange rate. We provide extensive empirical evidence for this signalling channel using micro data for firms in multiple emerging markets and event studies of local currency depreciation episodes
10.2139/ssrn.4029741
Keywords: Graue Literatur; signaling; Foreign currency debt; corporate debt; signalling; exchange rates; pecking order